Computer-Assisted Mathematics Instruction for Students With Specific Learning Disability: A Review of the Literature - Stultz, Sherry L. (Journal of special education technology, 2017)
This review was conducted to evaluate the current body of scholarly research regarding the use of computer-assisted instruction (CAI) to teach mathematics to students with specific learning disability (SLD). For many years, computers are utilized for educational purposes. However, the effectiveness of CAI for teaching mathematics to this specific group of students is unclear. First, a brief review of the diagnosis of SLD, the importance of mathematics instruction for these students, and the use of computers in the classroom is provided. Next, a review of the current body of research is presented. Finally, suggestions for future research are discussed. Since 1981, a total of 25 research studies have been published, focusing exclusively on using CAI for teaching mathematics to students with SLD. This review examines the current body of research for this area. In addition, the author provides recommendations for future research on this important subject for this category of students.